Effect of Wnt signaling pathway activation on the efficient generation of bovine intestinal organoids - Kang Won Park; Hyeon Yang; Hayeon Wi; Sun A Ock; Poongyeon Lee; In-Sul Hwang; Bo Ram Lee (Journal of Animal Reproduction and Biotechnology, 2022)
Recent progress has been made to establish intestinal organoids for an in vitro model as a potential alternative to an in vivo system in animals. We previously reported a reliable method for the isolation of intestinal crypts from the small intestine and robust three-dimensional (3D) expansion of intestinal organoids (basal-out) in adult bovines. The present study aimed to establish next-generation intestinal organoids for practical applications in disease modeling-based host-pathogen interactions and feed efficiency measurements. In this study, we developed a rapid and convenient method for the efficient generation of intestinal organoids through the modulation of the Wnt signaling pathway and continuous apical-out intestinal organoids. Remarkably, the intestinal epithelium only takes 3-4 days to undergo CHIR (1µM) treatment as a Wnt activator, which is much shorter than that required for spontaneous differentiation (7 days). Subsequently, we successfully established an apical-out bovine intestinal organoid culture system through suspension culture without Matrigel matrix, indicating an apical-out membrane on the surface. Collectively, these results demonstrate the efficient generation and next-generation of bovine intestinal organoids and will facilitate their potential use for various purposes, such as disease modeling, in the field of animal biotechnology.